Problemas de Fermi nas aulas de física : estratégias para resolução de problemas de estimativas - Santos, Renato Rodrigues dos (2017)
The aim of this research is to produce, apply and evaluate a didactic sequence, with the purpose of working numerical estimates in solving Fermi problems. The research has a qualitative character and was developed in a minicourse format, applied in a first-year High School class at IFPR Campus Paranavaí. The literature review listed elements about: Fermi's estimates, didactic sequences and David Ausubel's theory of meaningful learning. All these elements was used to guide the preparation of the activities developed, as well as to evaluate the results obtained. The results evidenced in this research indicate that students have developed different strategies to solve problems successfully. So, we considered that this type of problem can be useful as it allows students to reflect on their resolution, not only worrying about reaching a unique solution. The results were satisfactory because, although part of the students did not reach the objectives, it was possible to identify their difficulties and, thus, to propose interventions for the re-adaptation of the didactic sequence.